2014
DOI: 10.1111/pace.12530
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Regurgitation and Implantable Devices

Abstract: Cardiac device implantation was associated with a small but significant increase in the prevalence of moderate and severe TR, both acutely and chronically after implantation. The increase in TR was similar with both ICD and PPM placement, which was not related to the number of leads implanted and not associated with a significant increase in RVSP. Postimplantation TR was associated with a higher risk of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
85
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 17 publications
(33 reference statements)
12
85
2
7
Order By: Relevance
“…Similarly, a recent retrospective study by Al-Bawardy et al [18] reported that in addition to the trend with worsening TR, TR after cardiac device implantation was also associated with decreased survival. Our findings were also in line with the aforementioned data which clearly outline the detrimental effects of cardiac device implantation on tricuspid valve functions.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, a recent retrospective study by Al-Bawardy et al [18] reported that in addition to the trend with worsening TR, TR after cardiac device implantation was also associated with decreased survival. Our findings were also in line with the aforementioned data which clearly outline the detrimental effects of cardiac device implantation on tricuspid valve functions.…”
Section: Discussionmentioning
confidence: 80%
“…В настоящее время не существует еди-ной точки зрения о месте фиксации электрода в правом желудочке, однако, по мнению отдель-ных экспертов, в случаях, когда электрод поме-щен в апикальную позицию, повышается риск адгезии или повреждения задней створки ТК и, как следствие, развития ТР [9,33].…”
Section: Discussionunclassified
“…В то же время развитие у пациента выраженной недостаточно-сти представляет серьезную проблему. Во-пер-вых, ее наличие в целом связано со снижением выживаемости больных, в крайних случаях мо-жет потребоваться хирургическая коррекция [8][9][10][11][12]. Во-вторых, учитывая ежегодно увеличи-вающееся количество имплантируемых ЭКС, можно ожидать значительного увеличения чис-ла подобных осложнений в ближайшем буду-щем [13,14].…”
Section: Introductionunclassified
See 2 more Smart Citations